Optical solitons with bandwidth limited amplification in non-Kerr law media - Biswas, Anjan; Wheeler, Darius (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
This paper studies optical solitons with linear attenuation and bandpass filters. The Kerr and power laws of nonlinearity are considered. The governing equations are integrated by the aid of He’s semi-inverse variational principle. The parameter domains are identified.
Optica Applicata, Vol. 40, 2010, nr 4, s. 801-809
Keywords: optyka; integrable systems; partial differential equations; solitons in optical fibers; solitons in plasma; fiber optics; optical communications; pulse propagation and temporal solitons; Kerr effect; nonlinear optics